Clinical attachment loss and molecular profile of inflamed sites before treatment (Journal of Applied Oral Science, 2022)
Objective: To monitor early periodontal disease progression and to investigate clinical and molecular profile of inflamed sites by means of crevicular fluid and gingival biopsy analysis. Methodology: Eighty-one samples of twenty-seven periodontitis subjects and periodontally healthy individuals were collected for the study. Measurements of clinical parameters were recorded at day −15, baseline and 2 months after basic periodontal treatment aiming at monitoring early variations ofthe clinical attachment level. Saliva, crevicular fluid and gingival biopsies were harvested from clinically inflamed and non-inflamed sites from periodontal patients and from control sites of healthy patients for the assessment of IL-10, MMP-8, VEGF, RANKL, OPG and TGF-β1 protein and gene expression levels.Results:Baseline IL-10 protein levels from inflamed sites were higher in comparison to both non-inflamed and control sites (p<0.05). Higher expression of mRNA for IL-10, RANK-L, OPG, e TGF-β1 were also observed in inflamed sites at day −15 prior treatment (p<0.05). After the periodontal treatment and the resolution of inflammation, seventeen percent of evaluated sites still showed clinically detectable attachment loss without significant differences in the molecular profile. Conclusions: Clinical attachment loss is a negative event that may occur even after successful basic periodontal therapy, but it is small and limited to a small percentage of sites. Elevated inflammation markers of inflamed sites from disease patients reduced to the mean levels of those observed in healthy subjects after successful basic periodontal therapy. Significantly elevated both gene and protein levels of IL-10 in inflamed sites prior treatment confirms its modulatory role in the disease status.